2012
DOI: 10.2478/v10289-012-0016-8
|View full text |Cite
|
Sign up to set email alerts
|

Instrumental Insemination of Honey Bee Queens During Flight Activity Predisposition Period 2. Number of Spermatozoa in Spermatheca

Abstract: S u m m a r yThe effect of the instrumental insemination of honeybee queens after they performed their orientation flight or attempted to perform the flight, on the number of sperm in the spermatheca was observed. Naturally mated queens and instrumentally inseminated queens were examined. Queens were instrumentally inseminated under one of the following 4 circumstances: the instrumentally inseminated queens were either 7 day olds and had been given either a short or long-CO 2 treatment, or they were inseminate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 9 publications
3
5
0
Order By: Relevance
“…2). Our results also agreed with reports found in A. mellifera where number of stored sperm from instrumentally inseminated queen was not significantly lower than that of naturally mated queens (Cobey, 2007;Gerula et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…2). Our results also agreed with reports found in A. mellifera where number of stored sperm from instrumentally inseminated queen was not significantly lower than that of naturally mated queens (Cobey, 2007;Gerula et al, 2012).…”
Section: Discussionsupporting
confidence: 93%
“…In any case, further investigations are needed to highlight the extent of this phenomenon and to understand its causes. Substantial discrepancies in the average number of sperm found in each spermatheca are reported in the literature: 1 -8 million in queens just mated, with an average of 3.5 million during the life of the queen (Al-Lawati et al, 2009); 4.7 -5.3 million (Gerula et al, 2012); over 7 million (Bieńkowska et al, 2011). The average sperm number observed by us in newly mated queens, indicates that inadequate mating and/or that defective sperm transfer into the spermatheca occurred at least in a substantial part of the sampled queens as the figures of the first and the second quartiles suggest: 1,184,896 and 1,994,792 sperms, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on honey bee queen mating thus far suggest that carbon dioxide (CO 2 ; the anaesthetic used in instrumental insemination), physical manipulation of the genital opening, seminal volume, number of spermatozoa in spermatheca, and possibly components of the seminal fluid all play a role in causing post‐mating changes of NM queens, inseminated queens, or both (Richard et al ., ; Kocher et al ., , , ; Niño et al ., ; Gerula et al ., ). Previously, we demonstrated that CO 2 and physical manipulation of the genital opening alter queen sexual receptivity (as measured by mating flight attempts), induce ovary activation, and modify gene expression in the brain (Niño et al ., ).…”
Section: Introductionmentioning
confidence: 97%